The Human Genome Project: An Insight to the Homo Sapiens (International Journal of Engineering and Computer Science, 2016)
We are now living in the 21st century, where we know technology has revolutionised the way of living of human life to so much so that we are now looking forward to be technologically dependent enough to do even small tasks of simple life, to complex issues of human beings. The human genome project enhances the capabilities of human beings, towards a new era where we may have possibilities of tracing even the deadliest diseases and even dealing with it. In this paper, the human genome project is being explored to make assumptions of further researches and how far the issues of healthy human society could be established is estimated. The idea is to allow the experts reflect upon the intricate progressions of science into practices of genes, and improve tools that can map genes, with the simulation of information technology. Among the main goals of the Human Genome Project (HGP) was to develop new, better and cheaper tools to identify new genes and to understand their function